Effekte eines selbstgesteuerten Krafttrainings bei 6-12-jährigen Kindern - eine Pilotstudie - Nitzsche, N.; Lange, T.; Fröhlich, M. (Leipziger Sportwissenschaftliche Beiträge, 2013)
In addition to being a sports game, strength training as a lesson to boost motor performance is assigned a high degree of evidence. In principle, strength training interventions are controlled by specification of exercise parameters. A scientific desideratum exists as to the extent to which children and adolescents can regulate strength training based on self-regulated exercise stress and at the same time experiencing an increase in motor performance. Based on the study results, it can be concluded that a nine-week, self-controlled strength training for children and adolescents can have a positive effect on various strength parameters, with any possible transfer effects on explosive strength and balance ability not being evident.